Plan estratégico de desarrollo turístico sostenible de la parroquia Nuevo Paraíso cantón Nangaritza, provincia Zamora Chinchipe - Alvarado Alvarado, Sonia Tatiana (2014)
This project "Strategic Plan for Sustainable Tourism Development in the parish New Paradise", was initially developed to analyze the current situation of the parish where the destination general data concerning the physical domain spatial, socio-cultural, ecological exposed territorial, economic and political administrative productive. Subsequently, the tourism potential of the parish covering information on the offer of New Paradise knowing the existing actual and real tourist facilities (infrastructure) fate, just as tourism demand within this point analyzed the profile of tourists was analyzed was determined zoning and attractive; and the existing problems through community workshops which allowed developing the FODA analysis to know the problems in the sector in tourism was also identified. Finally, with raised and based FODA information, we proceeded to develop strategic guidelines for the development and approach programs and projects to exploit natural and cultural resources in a sustainable way through the implementation of PEDTS that would achieve a benefit to the community.